Trade Analysis of RCEP Member Countries Plus India: Have They Been Competing? - Susilo, Ignatia Bintang Filia Dei (WELFARE Jurnal Ilmu Ekonomi, 2021)
Regional Trade Agreements (RTAs) and Preferential Trade Agreements (PTAs) increased significantly. One of the most prominent PTA negotiation is Regional Comprehensive Economic Partnership Agreement (RCEP). When making arrangements, countries should consider its effect on current trade pattern. This research studies comparative advantage and its pattern for 10 countries involved in RCEP (Australia, China, Indonesia, Japan, Korea, Malaysia, New Zealand, Philippines, Singapore, Thailand) plus India. This study uses Revealed Symmetric Comparative Advantage (RSCA) to examine trade data from 2004-2019. The findings are: (i) Comparative advantages between some RCEP member countries’ plus India are relative similar. It should be a concern for those countries to maintain their product’s competitiveness; (ii) Several countries show relevance on the trade theories that country will export products which use abundant factors in its production. These conditions also match the theory of comparative advantage which stated that countries will export product which have comparative advantages and become specialized on those products; and (iii) All countries (except China) have concentration on the products with low comparative advantage. The standard deviation of RSCA scores remains constant overtime showing that difference in comparative advantages in each countries remain constant, but indicate slight downward trend for India, in which indicates despecialization.Jumlah Perjanjian Perdagangan Regional (Regional Trade Agreements/RTA) dan Perjanjian Perdagangan Preferensial (Preferential Trade Agreements/PTAs) meningkat signifikan. Salah satu negosiasi PTA yang terbesar adalah Regional Comprehensive Economic Partnership Agreement (RCEP). Dalam suatu perjanjian perdagangan, penting untuk mempertimbangkan pola perdagangan negara-negara yang terlibat. Penelitian ini mempelajari keunggulan komparatif dan pola perdagangan untuk 10 negara yang terlibat dalam RCEP (Australia, China, Indonesia, Jepang, Korea, Malaysia, Selandia Baru, Filipina, Singapura, Thailand) dan India. Penelitian ini menggunakan Revealed Symmetric Comparative Advantage (RSCA) untuk menguji data perdagangan tahun 2004-2019. Diperoleh bahwa: (i) Keunggulan komparatif antara beberapa negara anggota RCEP serta India relatif sama. Dengan demikian, penting bagi negara-negara tersebut untuk menjaga daya saing produknya; (ii) Beberapa negara menunjukkan relevansi dengan teori perdagangan bahwa negara tersebut akan mengekspor produk yang menggunakan faktor yang melimpah dalam produksinya. Kondisi ini juga sesuai dengan teori keunggulan komparatif yang menyatakan bahwa negara akan mengekspor produk yang memiliki keunggulan komparatif dan menjadi spesialis pada produk tersebut; dan (iii) Semua negara (kecuali China) memiliki konsentrasi pada produk dengan keunggulan komparatif rendah. Standar deviasi dari nilai RSCA relatif konstan sepanjang waktu menunjukkan konsistensi pola spesialisasi keunggulan komparatif di masing-masing negara terdapat sedikit pola penurunan untuk India, yang mengindikasikan terjadinya despesialisasi.